Some varieties of quartz at the epithermal silver occurrences of Tas-Kystabyt magmatic belt (Yakutia): textures, IR-spectra, X-ray luminescence - O. A. Sustavov (Известия высших учебных заведений: Геология и разведка)
Varieties of quartz at silver occurrence Aid and silver veins of gold-rare metals deposit Ergelyah are studied. New data on the textures of comb quartz and earlier not documented the late coarse-grained quartz is presented; the IR- and X-ray luminescence spectra are analyzed. The transitions in growth process of comb quartz from the nearselvedge small unsplit crystals to wider split parts of the individuals, elongated along the c-axis, and then to transparent heads of crystals is considered. The formation of transparent heads of comb quartz crystals is replaced by crystallization of coarse-grained unsplit faintly smoky quartz, filling the axial parts of veins. The OH (Li) absorption band is typical in the IR-spectmm of comb quartz, which is usual to radiation citrine quartz, and the X-ray luminescence is in the field of 390-415 nm. Later unsplit coarse-grained quartz is characterized by the absence of OH (Li) absorption band in the IR-spectmm, and X-ray luminescence in the field of 530-535 nm.